Responses of cadmium exposures on growth, physio-biochemical characteristics and the antioxidative defence system of soybean (Glycine max L.) - Nikhat Manzoor1*, Mahmooduzzafar2*, Ruchi Srivastava1, Riyazuddeen Khan2 (Journal of Phytology, 2011)
Soybean (Glycine max L.) plants were subjected to different levels of cadmium (Cd) viz. 0.0 (control), 0.05, 0.10, 0.50, 1.00 and 2.00 mM from CdCl2. Exposure to different Cd levels severely inhibited the growth of the plants evaluated in terms of shoot and root lengths, shoot fresh and dry weights. Total chlorophyll content, nitrate reductase activity and total protein content reduced due to various Cd treatments. Non-enzymatic antioxidants such as total ascorbate and glutathione contents increased on occurrence of Cd stress. Cd enhanced lipid peroxidation rate as evident by the TBRAS content. Also, Cd activated the activities of catalase (CAT), peroxidase (APX) and superoxide dismutase (SOD) enzymes in the treated plants. The results suggest that the Cd exposures adversely affected the plant growth, however elicited non-enzymatic as well as enzymatic antioxidants to cope with the harmful consequences of the heavy metal.